Construction of Listeria monocytogenes Mutants with In‐Frame Deletions in the Phosphotransferase Transport System (PTS) and Analysis of Their Growth under Stress Conditions. Issue 9 (2nd August 2013) - Liu, Yanhong; Ceruso, Marina; Jiang, Yuji; Datta, Atin R.; Carter, Laurenda; Strain, Errol; Pepe, Tiziana; Anastasi, Aniello; Fratamico, Pina
Abstract: Listeria monocytogenes is a foodborne pathogen that is difficult to eliminate due to its ability to survive under different stress conditions such as low pH and high salt. To better control this pathogen in food, it is important to understand its survival mechanisms under these stress conditions. LMOf2365_0442, 0443, and 0444 encode for phosphotransferase transport system (PTS) permease (fructose‐specific IIABC components) that is responsible for sugar transport. LMOf2365_0445 encodes for glycosyl hydrolase. These genes were induced by high pressure and inhibited under salt treatments; therefore, we hypothesized that genes encoding these PTS proteins may be involved in general stress responses. To study the function of these genes, deletion mutants of the PTS genes ( LMOf2365_0442, LMOf2365_0443, and LMOf2365_0444) and the downstream gene LMOf2365_0445 were created in L. monocytogenes strain F2365. These deletion mutants were tested under different stress conditions. The growth of ∆LMOf2365_0445 was increased under nisin (125 μg/mL) treatments compared to the wild‐type ( P < 0.01). The growth of ∆LMOf2365_0442 in salt (brain–heart infusion medium with 5% NaCl) was significantly increased ( P < 0.01), and ∆LMOf2365_0442 showed increased growth under acidic conditions (pH 5.0) compared to the wild‐type ( P < 0.01). The results from phenotypic arrays demonstrated that some of these mutants showed slightly slower growth under different carbon sources and basic conditions. The results indicate that deletion mutants ∆LMOf2365_0442 and ∆LMOf2365_0445 were more resistant to multiple stress conditions compared to the wild‐type, suggesting that they may contribute to the general stress response in L. monocytogenes . An understanding of the growth of these mutants under multiple stress conditions may assist in the development of intervention strategies to control L. monocytogenes in food.